Elasto-plastic soil structure analysis by BEM-FEM substructure method. - Zarco, Mark A. (Philippine Engineering Journal)
A method for solving soil structure interaction problems which indicates the infinite boundary effects of the far field domain is developed. The method involves coupling boundary elements based on the Melan fundamental solution with finite elements in a manner so as to result in a system of equations which is both symmetric and banded. Analyses of nonlinear soil structure interaction problems such as bearing capacity, lateral earth pressure and U-frame lock construction problems are performed to investigate the far field domain effect.